Students' Perceptions of the Islamic Inheritance Law Course and the Challenges Encountered - Rozikin, Mokhamad Rohma; Hamidah, Tutik; Ulum, Mohammad Samsul; Jamilah (International Journal Labs, 2025)
Islamic inheritance law is a critical subject within legal education, particularly for prospective lawyers and Muslim communities. However, many students at Universitas Brawijaya perceive this subject as complex and difficult to master. This study aims to explore students' perceptions of Islamic inheritance law and identify the key challenges they face in understanding it. A mixed-method approach was employed, combining quantitative data from Likert-scale questionnaires and qualitative input from open-ended responses. The study involved 182 active law students selected using the Isaac and Michael sampling formula. Results indicate that while students generally acknowledge the importance of the subject, they struggle with its complexity, abstract terminology, mathematical calculations, unstructured content, lack of Arabic proficiency, inadequate instructional strategies, and limited media support. Despite these barriers, a significant portion of students remain optimistic about mastering the subject. The findings highlight the need for empirically designed instructional models, practical learning tools, and improved pedagogical strategies. The implications of this study are essential for legal education reform, particularly in enhancing teaching effectiveness, student engagement, and professional competence in dealing with Islamic inheritance disputes.